Pengaruh Ukuran Perusahaan, Profitabilitas, Financial Leverage, dan Winner/Loser Stock pada Perataan Laba Perusahaan Manufaktur - Adriani, Putu Intan; Dwija Putri, I G.A.M Asri; Tenaya K., Gede Agus Indra (E-Jurnal Akuntansi; Vol 25 No 3 (2018)DO - 10.24843/EJA.2018.v25.i03.p11, 2018)
This research was conducted at a manufacturing company listed on Indonesia Stock Exchange (BEI) during the period 2013-2016. The number of samples used are 37 companies selected through purposive sampling method with 4 years of observation so that the total sample used to be 148 samples. . The Eckel Index is used as a distinguishing indicator between firms that do income smoothing and do not make income smoothing. Data collection was done by non participant observation method. Data analysis technique used is logistic regression. Based on the results of analysis in this study indicate that profitability variables affect the income smoothing, while the variable size of the company, financial leverage, and winner/loser stock has no effect on income smoothing. Keywords : Firm size, profitability, financial leverage, winner/loser stock, income smoothing.